"As Diverse as Possible": How Universities Compromise Multiracial Identities. Issue 1 (January 2023) - Giebel, Sonia
U.S. colleges and universities are under increasing pressure to appear racially diverse, but have yet to account systematically for a quickly growing contingent of multiracial-identifying students. Drawing on interviews with multiracial-identifying undergraduates at Western University, I demonstrate how everyday university practices compromise multiracial identities in the pursuit of diversity. The term compromise carries dual meaning, referring to instances where Western refashioned multiracial identities into monoracial ones and instances where multiracial-identifying students were in compromised positions. Participants inferred how their identities might be most useful to the university in appearing diverse, leading them to question their belonging and even recast their identities accordingly. These interactions occurred across organizational contexts, including dorms, community centers, and classrooms. Persistent organizational representations of diversity in monoracial terms communicates to students that multiracial identities are both a challenge to accommodate and of potential utility to institutions seeking to appear as diverse as possible.